2007
DOI: 10.1177/147470490700500310
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Romantic Kissing among College Students: An Evolutionary Perspective

Abstract: This study provides a descriptive account of kissing behavior in a large sample of undergraduate college students and considers kissing in the context of both short-term and long-term mating relationships. Kissing was examined as a mate assessment device, a means of promoting pair bonds, and a means of inducing sexual arousal and receptivity. A total 1,041 college students completed one of three questionnaires measuring kissing preferences, attitudes, styles, and behaviors. Results showed that females place mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 40 publications
2
47
0
1
Order By: Relevance
“…It has also previously been found that romantic kissing is used in assessing a mating partner's desirability (Hughes et al 2007;Wlodarski and Dunbar 2013). The results of the current study synthesize these findings by showing that attitudes towards romantic kissing vary across the menstrual cycle and are significantly associated with the fluctuation of menstrual hormones.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…It has also previously been found that romantic kissing is used in assessing a mating partner's desirability (Hughes et al 2007;Wlodarski and Dunbar 2013). The results of the current study synthesize these findings by showing that attitudes towards romantic kissing vary across the menstrual cycle and are significantly associated with the fluctuation of menstrual hormones.…”
Section: Discussionsupporting
confidence: 78%
“…The first component, relating to "sensory factors," implies that sensations involving smell contribute in a similar way to making someone a good kisser, possibly because these cues can be used to make inferences about the underlying mate quality or genetic suitability using pheromonal cues or on signals of general health (Durham et al 1993;Wedekind et al 1995). The second PCA factor related to contact/arousal themes, which have been proposed as another possible function of kissing promoting partner arousal and the initiation of sexual relations (Hughes et al 2007). The final PCA factor appears to be related to kissing technique and may also be indicative of mate quality in certain situations, as research in related fields suggests that the quality of execution of complicated behavioral rituals (such as dancing) may be a cue to underlying genetic quality (Hugill et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From kissing and handholding to receiving oral sex -to various forms of vaginal intercourse -sexual acts in humans have important implications for understanding our complex mating psychology (see Fisher, 1994Fisher, , 2004. Some sexual acts seem to be an important part of human courtship -such as kissing (Hughes, Harrison, and Gallup, 2007). In fact, Miller (2000) argues that all sexual acts that take place in the early part of forming a pairbond have an important role in mateassessment.…”
mentioning
confidence: 99%
“…Kissing a woman may be an effective flirtation act for men because it allows a woman to assess the parental investment potential of the man. Hughes et al (2007) report that via chemosensory analysis of the saliva in a male's kiss and via the wetness of a man's kiss women are able to ascertain a male's genetic and parental investment potential.…”
Section: Discussionmentioning
confidence: 99%